Time Series Analysis of Chromophoric Dissolved Organic Matter (CDOM) at Perancak Estuary - Suryaputra, I Gusti Ngurah Agung (International Journal of Natural Science and Engineering, 2023)
This study aimed at determaining the effect of sea tides on  changes of CDOM,  in-situ parameters and  nutrients on Perancak Estuary. The subject of  this study was estuary water collected from Estuary Perancak and filtered using GF/F 0.7 μm with help of injection. The objects of this study were CDOM absorbance, nutrients concentration and parameters in-situ. Sampel collected every 1 hour  once for 25 hours, were measured in-situ parameters. Filtered estuary water was placed into sample bottles and placed in a box  was kept away from light. Absorbance and nutrients concentration were measured  using  UV-1800 Shimadzu UV-Vis Spectrophotometer. Absorbance spectral slope (S) and  E2:E3 were calculated from the absorbance. Result shows that S275-295 and E2:E3 had  a negative correlation  with water level, while SR did not show any positive and negative correlation  with water level.  In addition most of  in-situ  parameters show a positive correlation with  water level and some of nutrients show a negative correlation with water level.